Arabic Language Curriculum For Non-Native Speakers (Descriptive Study of The Arab Intensive Arab Language Course at The University of Darussalam Gontor) - Alif Cahya Setiyadi; Subli Ansyah (Educan : Jurnal Pendidikan Islam, 2019)
This research is the implementation of the Arab Intensive Arab LanguageCourse at the University of Darussalam Gontor. The Arab Week, the Arabiclanguage program for students in the bilingual class at the Junior State Junior HighSchool, which was implemented one week ago by the Center for Courses andTraining at the University of Darussalam Gontor, limits the implementation of thisprogram to one point on the development of speech skills among learners. Thepurpose of this research is to reveal the programs, activities and methods ofapplying them and the curriculum of teaching Arabic language. This research wasbased on the Descriptive Analisis Method to describe the phenomena in the field ofresearch. The data in this research are collected through the observation, interview and written documents. The result of this study was that the intensive Arab week in Arabic was conducted over the course of the week, using the school curriculum andthe intensive curriculum, or the school curriculum is to teach the Arabic language inthe classroom due to the study materials in the school, The Arabic languagelearning program is limited to one week, one month or one year and focuses onsome of the four language skills.